Epistemic decolonisation in reconstituting higher education pedagogy in South Africa: the student perspective. Issue 7 (17th November 2021) - Motala, Shireen; Sayed, Yusuf; de Kock, Tarryn
ABSTRACT: This paper seeks to understand how the curriculum is experienced across two higher education institutions to probe students' understandings of epistemic access in the context of decolonisation debates. Three particular aspects of student experience of the decolonised curriculum and pedagogy are scrutinised. First, we look at the kind of sociality encouraged in the pedagogic encounter. Since a core function of education is social and cultural formation, a question arises as to what kind of sociality is possible between students and lecturers in a decolonised education space, including in the context of COVID-19. Second, we explore patterns of participation including, academic activities and support provided. Third, we investigate the knowledge forms and canon to which students are exposed in their respective programmes, with consideration of language issues. Finally, we examine the decolonisation of the curriculum in the context of the Covid-19 pandemic.